Prison writing and the literary world: imprisonment, institutionality and questions of literary practice - Kelly, Michelle; Westall, Claire (Routledge interdisciplinary perspectives on literature, 2021)
"Prison Writing and the Literary World tackles international prison writing and writing about imprisonment in relation to questions of literary representation and formal aesthetics, the "value" or "values" of literature, textual censorship and circulation, institutional networks, and literary-critical methodologies"--